Moringa oleifera and autophagy: evidence from in vitro studies on chaperone-mediated autophagy in HepG₂ Cancer cells - Bopape, Matlola; Tiloke, Charlette; Ntsapi, Claudia (Taylor and Francis Group, 2023)
Hepatocellular carcinoma (HCC) is the most prevalent primary liver cancer in Sub-Saharan African countries, including South Africa (SA). Given the limitations in current HCC therapeutics, there is an increasing need for alternative adjuvant therapeutic options. As such, several cell survival mechanisms, such as autophagy, have been identified as potential adjuvant therapeutic targets in HCC treatment. Of the three most established autophagic pathways, the upregulation of chaperone-mediated autophagy (CMA) has been extensively described in various cancer cells, including HCC cells. CMA promotes tumor growth and chemotherapeutic drug resistance, thus contributing to HCC tumorigenesis. Therefore, the modulation of CMA serves as a promising adjuvant target for current HCC therapeutic strategies. Phytochemical extracts found in the medicinal plant, Moringa oleifera (MO), have been shown to induce apoptosis in numerous cancer cells, including HCC. MO leaves have the greatest abundance of phytochemicals displaying anticancer potential. However, the potential interaction between the pro-apoptotic effects of MO aqueous leaf extract and the survival-promoting role of CMA in an in vitro model of HCC remains unclear. This review aims to summarize the latest findings on the role of CMA, and MO in the progression of HCC.